The Development of Teachers' and Their Students' Social and Emotional Learning During the “Learning to Be Project”-Training Course in Five European Countries - Berg, Minna; Talvio, Markus; Hietajärvi, Lauri; Benítez, Isabel; Cavioni, Valeria; Conte, Elisabetta; Cuadrado, Francisco; Ferreira, Marco; Košir, Matej; Martinsone, Baiba; Ornaghi, Veronica; Raudiene, Irena; et al. (Frontiers in Psychology, 2021)
In recent years, the school curricula in many European countries have introduced social and emotional learning (SEL). This calls for the teachers to have SEL competencies. The present study evaluates teachers´ and their students´ readiness for SEL during an intervention in five European countries. The participants were teachers (n = 402) in five European countries; Italy, Latvia, Lithuania, Slovenia and Spain. The pre- and post measuring points for both the intervention and the comparison group were at approximately the same time before and after the intervention. Comparison data consisted of 159 teachers in the same countries. The training for the intervention group lasted 16 hours for the teachers and a maximum of 16 hours for the principles and headmasters. An additional 9 hours of further monitoring took place. There were two student groups participating in the study: the age group of 8-11 years (pre puberty) and the age group of 12-15 –years (adolescents). Students, whose teachers had participated in the intervention, formed the intervention group (n =2552). Those students, whose teachers did not participate in the intervention, formed the comparison group (n = 1730). The questionnaire data were collected at the beginning and at the end of the school year for both age groups. The results indicated that there was a favorable development in the intervention group in some of the measured skills among students, but the effects were different for the two age groups. This study adds to both theoretical and practical development of continuing teacher training about SEL and its possible role in reducing problem behavior among the students.